If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 4) + -2x = 3(2 + -4x) Reorder the terms: 3(4 + 2x) + -2x = 3(2 + -4x) (4 * 3 + 2x * 3) + -2x = 3(2 + -4x) (12 + 6x) + -2x = 3(2 + -4x) Combine like terms: 6x + -2x = 4x 12 + 4x = 3(2 + -4x) 12 + 4x = (2 * 3 + -4x * 3) 12 + 4x = (6 + -12x) Solving 12 + 4x = 6 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 12 + 4x + 12x = 6 + -12x + 12x Combine like terms: 4x + 12x = 16x 12 + 16x = 6 + -12x + 12x Combine like terms: -12x + 12x = 0 12 + 16x = 6 + 0 12 + 16x = 6 Add '-12' to each side of the equation. 12 + -12 + 16x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + 16x = 6 + -12 16x = 6 + -12 Combine like terms: 6 + -12 = -6 16x = -6 Divide each side by '16'. x = -0.375 Simplifying x = -0.375
| 5[m+4]=-2[-4-m]+3 | | (5-5):(1/5) | | 2*3+5=360 | | 12v+14+-10v=80 | | 3x+63+6x+12=180 | | 5-5:1/5 | | ln(x-1)+ln(x+4)=ln(2(x+1)) | | 5-5/1/5 | | 11=-20+121 | | 92-(11+19)=51 | | 2(6-5p)-(8-9p)= | | 4(2x+1)(3x-9)=0 | | 100+10x=0+15x | | 6y+24x=48 | | 99999999+1= | | f(a)=6a-5 | | (2/3)^3x=8/27 | | 4x^4+3x+3=0 | | 9y+3x=-18 | | 2a-b+c=18 | | 2x+0.5x=0 | | 4x^2+9y^2-4x+12y+5=0 | | r=4g+rz | | 3(f-4)=-6 | | x+39+40+20=180 | | -3x-5x=-2x | | 10(s-9)=169 | | 16a^2*12a^5= | | 20+40+39+x=180 | | 2a-2=3a-1 | | x-4/6=3/7 | | 8x+14y=180 |